S8: Understanding Dementia, Neurodegenerative Disorders, and neuropsychiatric symptoms in Aging populations from La tin America - Acosta, Daisy; de Jesús Llibre Rodríguez, Juan; Sosa, Ana Luisa; Acosta, Isaac; Jimenez-Velasquez, Ivonne Z.; Llibre Guerra, Jorge J (International psychogeriatrics, 2024)
Objectives: Dementia presents a growing public health challenge globally and its impact is significantly pronounced in low and middle-income countries (LMICs), including those in Latin America. This symposium aims to present recent findings on the prevalence, impact, and underlying factors of cognitive impairment and neuropsychiatric symptoms in aging populations across Latin America, with a focus on culturally and regionally specific research findings. Methods: The symposium will consolidate data from the 10/66 Dementia Research Group, which has conducted extensive research across various Latin American countries. We integrate results from multiple investigations with over 12,000 elderly participants from six Latin American countries, utilizing cross-sectional and longitudinal Methodsologies. These studies employ the 10/66 Dementia Research Group protocols, among other internationally recognized diagnostic tools, to assess dementia, neurodegeneration and neuropsychiatric symptoms. Results: The symposium will delve into critical yet not well-understood topics. The audience will be first introduced to emerging trends of dementia prevalence and incidence in Latin America and the interaction with different risk factors particular to the region. Second, we will discuss findings from a comprehensive analysis focusing on the prevalence and impact of cognitive impairment and incident dementia in parkinsonism and Parkinson’s Disease. The third presentation will focus on the prevalence of neuropsychiatric symptoms across cognitively unimpaired, dementia, and Parkinson’s’ disease, emphasizing the need to implement systematic screening Methods for early detection from a clinical and public health perspective. The final talk will present data exploring the influence of genetic ancestry alongside social and environmental factors as predictors of dementia risk in Latin America. Conclusions: The findings presented underscore the complex interplay of genetic, social, and environmental factors in the etiology and progression of neurodegenerative and neuropsychiatric conditions in Latin America. The symposium will highlight the critical need for comprehensive public health strategies and enhanced research focus to better understand and address these issues within aging populations.